Method of managing the execution of tasks of a multithreaded program according to a given dependency graph - Nesterenko, K.P.; Stetsenko, I.V. (Інститут програмних систем НАН України, 2024)
Performance is one of the main non-functional requirements for software. As a result of the increase in the number of cores in central processing units in recent decades, the use of multithreading technology has become a primary means of improving software performance. This study analyzes the problems that arise from developing multithreaded programs and ways to address them. A method for managing the execution of tasks in a multithreaded program based on a given dependency graph is proposed and its implementation in the C++ language is demonstrated. Its aim is to reduce the resource intensity of software development and increase its reliability by addressing problems typical of developing multithreaded programs. The results of experimental research on a test set of tasks are provided, demonstrating increased performance through the use of the proposed method.Prombles in programming 2024; 2-3: 239-246